Decolonization of Staphylococcus aureus in patients with atopic dermatitis: a reason for increasing resistance to antibiotics? - Błażewicz, Izabela; Jaśkiewicz, Maciej; Bauer, Marta; Piechowicz, Lidia; Nowicki, Roman; Kamysz, Wojciech; Barańska-Rybak, Wioletta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2017)
Introduction : Exacerbation of atopic dermatitis can be associated with bacterial infection. The skin of patients is colonized with Staphylococcus aureus in 90% of cases. An attempt has been made to demonstrate that eradication significantly reduces the severity of the disease. Studies indicate the efficacy of topical antibiotics, topical corticosteroids and calcineurin inhibitors. Due to increasing resistance to drugs and the defective antimicrobial peptide profile, decolonization is virtually impossible. Aim : To determine the prevalence of S. aureus colonization among patients with atopic dermatitis and to assess antimicrobial susceptibility of isolated strains to antibiotics, especially fusidic acid and mupirocin. Material and methods : One hundred patients with atopic dermatitis and 50 healthy subjects were microbiologically assessed for the carriage of S. aureus . Antimicrobial susceptibility tests were performed using the broth-microdilution method for antibiotics: ampicillin, ciprofloxacin, daptomycin, erythromycin, fusidic acid, linezolid, lincomycin, mupirocin, tetracycline and vancomycin. Results : Staphylococcus aureus strains were isolated from the majority of our patients, either from the skin (71%) or the anterior nares (67%). In the present study, 10% of isolations represented methicillin-resistant S. aureus (MRSA). Antibiotics exhibited diverse activities against clinical isolates of S. aureus . Among those tested, the highest rates of resistance were shown for ampicillin – 58.5%, lincomycin – 37.5% and erythromycin – 31.0%. Enhanced resistance levels were expressed to mupirocin (17.5%) and fusidic acid (15.5%). Conclusions : According to the increasing rate of resistance and quick recolonization after discontinuation of the treatment, chronic use of topical antibiotics is not recommended and should be limited to exacerbation of atopic dermatitis with clinical signs of bacterial infection.